Distribution of two invasive alien diatom species Achnanthidium delmontii and Achnanthidium druartii in Slovenia - Aleksandra Krivograd Klemenčič; Tadeja Šter (Acta Biologica Slovenica)
The distribution of two invasive diatom species in Slovenia, Achnanthidium delmontii (ADMO) and Achnanthidium druartii (ADRU), was investigated in this study. Data from 87 rivers and 11 lakes collected between years 2019 and 2024 in the frame of national monitoring of ecological status of surface waters were included. ADMO was present in 46% of the rivers and was dominant (>5% relative abundance) in 27 rivers (31%), with the highest abundance reaching 77% in the Bolska River. It was rare in lakes, detected in only three lakes. ADRU was detected in 14% of the rivers and was dominant in four rivers, with the highest abundance reaching 27% in the Drava River. In contrast, ADRU was common in lakes (73%), dominating in the Lake Slivniško Jezero and the Lake Perniško jezero. ADMO presence was associated with reduced diatom species richness and evenness, although no direct ecological impact was observed. ADMO was present mainly in upper river sections, while ADRU was more frequent in lowland river sections, lakes and reservoirs. The results of this study confirmed the invasive character of ADMO, whereas ADRU did not affect species richness and evenness of the diatom assemblages, and thus its invasive character could not be confirmed.